2022-RA-1593-ESGO Isolated para-aortic lymph node metastases in high risk endometrial cancer. (20th October 2022) - Laseca, Maria; Arencibia, Octavio; González, Daniel; Rave, Andrés; Navarro, Beatriz; Ramchandani, Avinash; Martín, Alicia
Abstract : Introduction/Background: Direct metastases to the para-aortic lymph nodes in endometrial cancer are extremely rare. A direct route of lymphatic propagation from the uterus to the para-aortic nodes through the infundibulopelvic ligament has been suggested. The objective of this study was to determine the characteristics and 5 years overall survival of isolated para-aortic lymphatic metastases in high-risk endometrial cancer. Methodology: Retrospective study of patients with high-risk endometrial cancer was performed in a reference center in gynecological oncology. All patients underwent surgery including complete lymph node staging by pelvic and para-aortic lymphadenectomy. Patients were divided into three groups based on the patterns of lymphatic metastases: isolated para-aortic lymphatic metastases, isolated pelvic lymphatic metastases, and dual lymphatic metastases (pelvic and para-aortic metastases). Clinicopathological characteristics and 5-year survival were compared between the three groups. Results: 147 women diagnosed with high-risk endometrial cancer underwent surgery, performing pelvic and para-aortic lymphadenectomy during surgery. The mean age of the patients was 61.62 years. The most common histological type was endometrioid adenocarcinoma (37.4%), followed by serous carcinoma (31.3%). Regarding the histological grade, 77.6% was G3. The most frequent FIGO stage was IA (38.8%). Regarding lymph node dissemination, the proportion of patients with isolated para-aortic lymphatic metastases was 4.76% (n=8), isolated pelvic metastases 17.69% (n= 26) and dual metastases (pelvic and para-aortic) 7 .48% (n= 11). Patients with isolated pelvic lymphatic metastases and isolated para-aortic lymphatic metastases shared similar histologic features. The 5-year overall survival rate in the cohort of patients with isolated para-aortic nodes was 62.5% and 61.5% in the cohort of patients with isolated pelvic nodes. Overall survival in the cohort of patients with metastases duals was 36.4%. Conclusion: Patients with high-risk endometrial cancers with isolated lymphatic and para-aortic metastases and isolated pelvic metastases share similar clinical pathological features and prognoses.